PENGARUH KURS, SUKU BUNGA SERTIFIKAT BANK INDONESIA, INFLASI DAN INDEKS NIKKEI 225 TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA PADA TAHUN 2015-2017 - Nurhaidah Nurhaidah; Jeni Susyanti; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABTRACKFor three years starting from the 2015-2017 period the joint stock price index experienced fluctuations. In this study the author will discuss Exchange Rate, Bank Indonesia Certificate Interest Rate, Inflation and the Nikkei 225 Index which can affect the joint stock price index. The research of this paper uses Explanatory type. This research examines the population from sampling by using purposive sampling technique using two types of variables, namely Dependent Variables (dependent variable) and Independent Variables (independent variables). The results of this study are that the Exchange Rate variable has a significant effect on the JCI, the variable interest rate of Bank Indonesia Certificates has a significant effect on the JCI, the Inflation variable has a significant effect on the JCI, the Nikkei 225 Index has a significant effect on the JCI. Keywords: Exchange Rate, Bank Indonesia Certificate Interest Rate, Inflation, Nikkei 225 Index.